Overcoming Electrostatic Repulsions During Amyloid Assembly: Effect of Ph and Interaction with Divalent Metals Using Model Peptides - Diaz-Espinoza, R (Academic Press, 2017)
Amyloids are polypeptide aggregates involved in many pathologies including Alzheimer s disease. Amyloid assembly is a complex process affected by different interactions including hydrogen bonding, van der Waals forces and electrostatic interactions. The highly regular amyloid structure allows for an arrangement of residues that forces side chains to be closely positioned, giving rise to potentially unfavorable interactions such as electrostatic repulsions. In these cases, amyloid assembly will depend on a balance between stabilizing versus unfavorable interactions. In this study, we rationally designed several amyloid-prone model peptides that had two acidic groups and tested their assembly into amyloids under different conditions. We found that at low pH (pH 4.0), most peptides spontaneously formed amyloids whereas no or little aggregation was observed at higher pHs (pH 8.0). When divalent metals with affinity for carboxylate groups were added at millimolar concentrations, most peptides exhibited a metal-dependent switch to the amyloid state at pH 8.0. Our results show that electrostatic repulsion between amyloid-prone sequences can be overcome in conditions that affect protonation of residue side chains. Moreover, the presence of divalent metals can contribute to electrostatic shielding through specific coordination with acidic groups and thus promote amyloid assembly. © 2017 Elsevier Inc.